Unusual records of marine organisms in the Neretva River (Croatia and Bosnia and Herzegovina) - Tutman, Pero (Array, 2021)
This paper presents a review of the unusual occurrences of various marine species found upstream in the Neretva River and its wider delta zone in the last two decades. The occurrences of at least eight different marine species were reported by local fishermen, representing very rare records of these species in the upstream areas of rivers. Although some of these species generally inhabit both saltwater and brackish waters, their occurrences high upstream are probably the consequence of changes in hydrological conditions in Neretva River. Namely, more intense saltwater intrusion into the river observed in the last two decades provides suitable conditions for mass penetration of euryhaline organisms high into the Neretva River. In this biodiversity rich area which hosts a significant number of endemic species, such phenomena can threaten the local freshwater communities.